KEMAMPUAN PASAR MODAL DALAM MENGANTISIPASI KINERJA OPERASIONAL PERUSAHAAN DI MASA DATANG: DALAM KONTEKS EQUITY RIGHT ISSUE DI INDONESIA - Etty Indriani (Benefit: Jurnal Manajemen dan Bisnis, 2004)
The study addressed to: (1) investigated the market reaction toward right issue announcement;(2)gave an empirical evidence of association of stock market reaction with firm’s operational performance inthe future; (3) examined specific variables of right issue s that might explain the reaction of the stockmarket at the announcement and the operational performance of firms in the future. Result shows thatthe Indonesian stock market gave negative reaction on the third and fourth days after the right issueannouncement. So the stock market had late caught the information. Further, the firms did the rightissue s gained higher operating performance level in the second and third year than average level in theterms of firm operating performance in the same industry that did not do the right issue . The changes offirm’s operating performance in the future tend to the positive change. The issue-price was the specificvariable of the right issue that influenced positively on the abnormal return. Meanwhile, the issue-pricenegatively affected on the future firm’s operating performance. In the empirical evidence equity right issues, the stock market reaction might to anticipate the change of the future firm’s operating performancethrough the specific variable issue-price with opposite direction